Using miniature MS system with automatic blood sampler for preclinical pharmacokinetics study. (November 2017) - Pu, Fan; Zhang, Wenpeng; Bateman, Kevin P; Liu, Yong; Helmy, Roy; Ouyang, Zheng
Aim: Preclinical pharmacokinetic studies are an essential part of modern drug development. In this work, we explored a new solution with onsite analysis using a miniature MS system, which can significantly improve the efficiency of the preclinical study. Materials & methods: A miniature mass spectrometer was used with an automatic blood sampler for onsite quantitation of drug compounds in whole blood samples. Slug-flow microextraction was used to replace the in-lab sample preparation.Results & conclusion: Animal studies were carried out using two drug compounds, using the auto sampler to take blood samples at preprogrammed time points. The miniature MS system was used to obtain drug concentrations, which were subsequently used to calculate the pharmacokinetic parameters.